Numerical modeling for freezing and cryogenic preservation for viability of biological tissue. (2018) - Kundu, Pallab; Sukumar, S.; Kar, S.P.
Abstract: A numerical model has been developed to analyze the temperature distribution inside a biological tissue under cryogenic conditions. The energy equation is discretized using finite volume method (FVM). The left and right walls of the tissue have been subjected to cryogenic temperature of nitrogen while the top and bottom walls of the tissue have been insulated. Tri-Diagonal Matrix Algorithm (TDMA) has been used to solve the algebraic equation to find temperature distribution inside the tissue. The method is validated with experimental data from the existing literature. The enthalpy-porosity method has been employed to track the moving solid-liquid interface at different time inside the specimen and the position of solid-liquid interface has plotted at different time. The position of velocity vectors have been also plotted at different time. As the convective cooling proceeds, it has been seen that the velocity current shrinks before finally seizing to exist.